Minding the Ecological Body: Neuropsychoanalysis and Ecopsychoanalysis - Dodds, Joseph (Frontiers in Psychology, 2013)
Neuropsychoanalysis explores experimentally and theoretically the philosophically ancient discussion of the relation of mind and body, and seems well placed to overcome the problem of a 'mindless' neuroscience and a 'brainless' psychology and psychotherapy, especially when combined with a greater awareness that the body itself, not only the brain, provides the material substrate for the emergent phenomenon we call mind. However, the mind-brain-body is itself situated within a complex ecological world, interacting with other mind-brain-bodies and the 'non-human environment'. This occurs both synchronically and diachronically as the organism and its environment (living and nonliving) interact in highly complex often nonlinear ways. Psychoanalysis can do much to help unmask the anxieties, deficits, conflicts, phantasies and defences crucial in understanding the human dimension of the ecological crisis. Yet, psychoanalysis still largely remains not only a 'psychology without biology', which neuropsychoanalysis seeks to remedy, but also a 'psychology without ecology'. Ecopsychoanalysis (Dodds & Jordan 2012) is a new transdisciplinary approach drawing on a range of fields such as psychoanalysis, psychology, ecology, philosophy, science, complexity theory, aesthetics, and the humanities. It attempts to play with what each approach has to offer in the sense of a heterogeneous assemblage of ideas and processes, mirroring the interlocking complexity, chaos and turbulence of nature itself. By emphasizing the way the mind-brain-body studied by neuropsychoanalysis is embedded in wider social and ecological networks, ecopsychoanalysis can help open up the relevance of neuropsychoanalysis to wider fields of study, including those who are concerned with what E.O. Wilson (2003) called 'the future of life’.